Pastor Peter Rosing with his wife and daughters, Angmagssalik 1930. Peter Rosing, Svend Peter K... : Pastor Peder Rosing med hustru og døtre, Angmagssalik 1930. Peter Rosing, Svend Peter Kristian Rosing, 9.1.1892-27.8.1965, maler. Født i Godthåb, død i Jakobshavn. R. blev dimitteret fra Godthåb seminarium 1915 og efter videreuddannelse i Danmark virkede han som overkateket, indtil han 1918 blev ordineret som præst i Egedesminde, fra 1920 i Godhavn. 1922 blev han sendt til Østgrønland for at afløse faderen som missionær i Angmagssalik hvor han indtil 1934 videreførte dennes arbejde blandt de nydøbte østgrønlændere - Petersen, Sofie (University of Southern California Digital Library (USC.DL), 2015)
Pastor Peter Rosing with his wife and daughters, Angmagssalik 1930. Peter Rosing, Svend Peter Kristian Rosing, 9.1.1892-27.8.1965, painter. Born in Godthåb, died in Jakobshavn. R. graduated from Godthåb Seminary in 1915 and after training in Denmark he worked as a catechist until he in 1918 was ordained as a priest in Egedesminde, 1920 in Godhavn. In 1922 he was sent to East Greenland to replace his father as a missionary in Angmagssalik which he in 1934 continued his work among the newly baptized East Greenlanders